2022 roadmap on low temperature electrochemical CO2 reduction. (1st October 2022) - Stephens, Ifan E L; Chan, Karen; Bagger, Alexander; Boettcher, Shannon W; Bonin, Julien; Boutin, Etienne; Buckley, Aya K; Buonsanti, Raffaella; Cave, Etosha R; Chang, Xiaoxia; Chee, See Wee; da Silva, Alisson H M; et al.
Abstract: Electrochemical CO2 reduction (CO2 R) is an attractive option for storing renewable electricity and for the sustainable production of valuable chemicals and fuels. In this roadmap, we review recent progress in fundamental understanding, catalyst development, and in engineering and scale-up. We discuss the outstanding challenges towards commercialization of electrochemical CO2 R technology: energy efficiencies, selectivities, low current densities, and stability. We highlight the opportunities in establishing rigorous standards for benchmarking performance, advances in in operando characterization, the discovery of new materials towards high value products, the investigation of phenomena across multiple-length scales and the application of data science towards doing so. We hope that this collective perspective sparks new research activities that ultimately bring us a step closer towards establishing a low- or zero-emission carbon cycle.